Early Child Care and Labor Supply of Lower-SES Mothers: A Randomized Controlled Trial - Henning Hermes; Marina Krauß; Philipp Lergetporer; Frauke Peter; Simon Wiederhold (Institute of Labor Economics (IZA), 2022)
We present experimental evidence that enabling access to universal early child care for families with lower socioeconomic status (SES) increases maternal labor supply. Our intervention provides families with customized help for child care applications, resulting in a large increase in enrollment among lower-SES families. The treatment increases lower-SES mothers' full-time employment rates by 9 percentage points (+160%), household income by 10%, and mothers' earnings by 22%. The effect on full-time employment is largely driven by increased care hours provided by child care centers and fathers. Overall, the treatment substantially improves intra-household gender equality in terms of child care duties and earnings.
Keywords: D90; J13; J18; J22; C93; 330; gender equality; maternal employment; child care; randomized controlled trial